Operational performance and longitudinal distribution of seeds by precision seeder submitted to different calibrations of the wheel - Correia, Tiago Pereira da Silva; Lopes, Arthur Gabriel Caldas; Tavares, Leandro Augusto Felix; Taveira, Wesley Matheus Cordeiro Fulgêncio; Silva, Paulo Roberto Arbex [UNESP] (Nativa, 2020)
The settings of the seeder-fertilizer are crucial for the correct distribution of inputs, thus improving operational performance. The objective of the work was to evaluate the longitudinal distribution of seeds and the operational performance of a precision seed drill-fertilizer in function of different tire insufflation pressures. The experimental design used was randomized blocks, with three tire insufflation pressures from the seeder-fertilizer (138, 241 and 345 kPa), repeated in six blocks, totaling 18 plots of 60 m long and 4.5 m wide each. Hourly fuel consumption (Chc), operational speed (V), tire slip (DP), operational field capacity (Cco), distance between seeds (DES), variation coefficient of spacing between seeds were performed (CVes) and distribution accuracy index (IP). The data were subjected to analysis of variance and the means compared by the Tukey test (P ≤ 0.05). The results indicated higher Chc and DP by the 345 kPa pressure. Minor failure, double, CVes, and higher IP, were obtained by pressure 241 kPa. Cco did not differ. It should be noted that for each type of machine and soil surface condition, refinement of tire pressure and machine adjustments is necessary.
Desempenho operacional e distribuição longitudinal de sementes por semeadora de precisão submetida à diferentes calibragens do rodado
Keywords: fuel consumption; insufflation; plantability; pressure; skating